Revitalization of Culture of Manners in the Era of Information Technology in the Dynamics of Using Social Media - Argarini, Fitri (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The complexity and context of this phenomenon are revealed through content analysis of literature and social media. This qualitative study investigates the phenomenon of cultural revitalization in the computer and internet era. In addition, this research will look at how social media influences sociocultural interactions. Research shows that social media has not only changed the way people interact with each other but has also become a place for activism, participation in politics, and developing creative ideas in the economic field. It influences sociocultural dynamics in a very complex way, which requires approaches from various scientific disciplines, such as anthropology, sociology, psychology, economics, and sociocultural political science. In conclusion, studying how social media influences society is an in-depth and complex study. Therefore, to understand how social media affects society, we need to have a broad understanding so that we can lead the revitalization of digital culture towards positive and sustainable development. The phenomenon of cultural revitalization that occurs in the digital era is the main focus of this research. This phenomenon represents a significant transformation in the way society uses, creates, and understands culture. Social media is an integral part of digital culture and plays a vital role in changing the social and cultural dynamics of society. Consequently, it is essential to understand how these changes affect people's daily lives, sociocultural frameworks, and interactions throughout the world.